Analisis Hukum Pembangunan Berkelanjutan Ibu Kota Nusantara (IKN) dalam Manajemen Risiko Pengembalian Investasi Asing - Ade Andrian Nur Satiaputra; Cika Silvia Puspa Christina; Nurhayani Butar Butar; Sunardi, Sunardi; Budi Prabowo; Rahajeng Oktovione Putri Bestari (UNES Law Review, 2024)
The implementation of infrastructure development in the Indonesian Capital City (IKN) is one of the government's strategic directions regulated in the provisions of Law no. 3 of 2022 concerning the Indonesian Capital City (IKN Law). One of the funding sources regulated in the IKN Law is the distribution of foreign funds, including the Government and Business Entity Cooperation (KPBU) program, financial support or international funding programs, and creative funding programs. The two research formulations focus on a critical study of risk management in relation to foreign investment returns in infrastructure development in the IKN. This research is a type of normative legal research with a sociological approach. The conclusion of this study is that the KPBU system has clearer accountability rules, but the use of the other two foreign investment systems is relatively faster to use. Therefore, the other two schemes require more configuration.